THE EFFECT OF BUGNET EXERCISE AND WILLIAM FLEXION EXERCISE ON PAIN REDUCTION IN LOW BACK PAIN PATIENTS - Massakuta, Nana Aulia (MACCA : Science-Edu Journal, 2024)
Low Back Pain (LBP) is a pain syndrome that occurs in the lower waist region and is a work releated musculoskeletal disorders. LBP is pain that is felt in the lower hip area, which is local or radicular pain or both. Method: This study using a pre-experimental design with a one-group pretest posttest design method which aims to determine the effect of giving microwave diathermy, bugnet exercise and william flexion exercise on reducing pain in patients with low back pain which was carried out at Inggit Medical Center Makassar with a population of 35 people with low back pain cases and a sample of 10 respondents in one treatment group that is Bugnet Exercise and William Flexion Exercise. The measuring instrument used is the Oswetry Disability Index (ODI). Results: The results of this study based on the Wilcoxon test obtained p value = 0.005 (p <0.05) with a mean reduction in pain after the treatment of 15.00 from the pretest value of 54.80 and then decreased to 39.80. This means that, Bugnet Exercise and William Flexion Exercise can have a significant effect on changes in pain levels in Low Back Pain sufferers. Conclusion: The conclusion of this study is that giving bugnet exercise and william flexion exercise can produce a significant effect on reducing pain in patients with low back pain.